Social Media Optimization for Branding MSMEs - Yuniarti, Rizki (Dinasti International Journal of Digital Business Management, 2024)
The significance of branding for MSMEs lies in its ability to help businesses stand out in a competitive market. By applying effective branding strategies—such as selecting the right social media platforms, maintaining consistent brand visuals, creating high-quality content, utilizing paid advertisements, and collaborating with influencers—MSMEs can significantly boost their sales. Building brand awareness for products and services is key to achieving success on social media, allowing MSMEs to grow and maintain sustainability. This study aims to explore how MSMEs can optimize social media for branding, analyze its effects on product visibility and sales, and identify the factors that contribute to successful social media branding. The research employs a descriptive method with a qualitative approach, using secondary data from the Ministry of Cooperatives and SMEs, the Indonesian Internet Service Providers Association (APJII), and relevant research studies.